TECHNOLOGY-ENABLED MOTION SENSING AND ACTIVITY TRACKING FOR REHABILITATION - ZHAO, WENBING (INST OF ENGIN AND TECH, 2023)
This book concentrates on sensing and measurement technologies for rehabilitation applications. The book looks at motion sensing technologies, human motion and exogames and healthcare applications including speech, respiration, and recovery from stroke or accident.
Keywords: Motion detectors.; Machine learning.; Medical rehabilitation.; elektronické knihy; electronic books